Cone Photoreceptors in Diabetic Patients - Elsner, Ann E.; Walker, Brittany R.; Gilbert, Robert N.; Parimi, Vamsi; Papay, Joel A.; Gast, Thomas J.; Burns, Stephen A. (Frontiers in Medicine, 2022)
Purpose: Cones in diabetic patients are at risk due to metabolic and vascular changes. By imaging retinal vessel remodelling at high magnification, we reduced its impact on cone distribution measurements. The retinal vessel images and retinal thickness measurements provided information about cone microenvironment. Methods: We compared cone data in 10 diabetic subjects (28-78 yr to our published norms from 36 younger and 10 older controls. All subjects were consented and tested in a manner approved by the Indiana University Institutional Review Board, which adhered to the Declaration of Helsinki. Custom adaptive optics scanning laser ophthalmoscopy (AOSLO) was used to image cones and retinal microcirculation. We counted cones in a montage of foveal and temporal retina, using 4 non-contiguous samples within 0.9 to 7 deg that were selected for best visibility of cones and least pathology. The data were fit with a 2 parameter exponential model: ln(cone density) = a * microns eccentricity + b. These results were compared to retinal thickness measurements from SDOCT. Results: Diabetic cone maps were more variable than in controls and included patches of unusually bright and dark cones, centrally and more peripherally. Model parameters and total cones within the central 14 deg of the macula differed across diabetic patients. Total cones fell into two groups: similar to normal for 5 vs. less than normal for 2 of 2 younger diabetic subjects and 3 older subjects low but not outside the confidence limits. Diabetic subjects all had retinal vascular remodeling to varying degrees: microaneurysms; capillary thickening, thinning, or bends; and vessel elongation including capillary loops, tangles, and collaterals. Yet SD-OCT showed that no diabetic subject had a Total Retinal Thickness in any quadrant that fell outside the confidence limits for controls. Conclusions: AOSLO images pinpointed widespread retinal vascular remodeling in all diabetic eyes, but the SDOCT showed no increased retinal thickness. Cone reflectivity changes were found in all diabetic patients, but significantly low cone density in only some. These results are consistent with early changes to neural, glial, or vascular components of the retinal without significant retinal thickening due to exudation.